ChemInform Abstract: Furo‐ and Thieno‐Fused 1, 3‐Diazepine‐4, 6‐diones. Issue 13 (1st April 2014) - Ozer, Merve Sinem; Koza, Gani; Sahin, Ertan; Balci, Metin
Abstract Starting from the furan (I) possessing two adjacent ester groups the synthesis of furo‐fused diazepinedione derivatives (VI) and (VII) is developed.